2014
DOI: 10.1016/j.molmet.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mitochondrial uncoupler that does not depolarize the plasma membrane

Abstract: Dysregulation of oxidative phosphorylation is associated with increased mitochondrial reactive oxygen species production and some of the most prevalent human diseases including obesity, cancer, diabetes, neurodegeneration, and heart disease. Chemical 'mitochondrial uncouplers' are lipophilic weak acids that transport protons into the mitochondrial matrix via a pathway that is independent of ATP synthase, thereby uncoupling nutrient oxidation from ATP production. Mitochondrial uncouplers also lessen the proton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
179
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 193 publications
(207 citation statements)
references
References 32 publications
11
179
0
Order By: Relevance
“…SR4 Increases Mitochondrial ROS Production-Previous studies have shown that some protonophore uncouplers can increase ROS production, whereas others do not (23,38,45). We assessed the ROS production in HepG2 cells using MitoSox TM Red fluorescence.…”
Section: Sr4 Disrupts Mitochondrial Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…SR4 Increases Mitochondrial ROS Production-Previous studies have shown that some protonophore uncouplers can increase ROS production, whereas others do not (23,38,45). We assessed the ROS production in HepG2 cells using MitoSox TM Red fluorescence.…”
Section: Sr4 Disrupts Mitochondrial Functionmentioning
confidence: 99%
“…Mitochondrial swelling was measured in non-respiring mouse liver mitochondria incubated in buffered isotonic potassium acetate in the presence of valinomycin as described (37,38). Briefly, isolated liver mitochondria were added to 1 ml of isotonic acetate buffer (145 mM potassium acetate, 5 mM TrisHCl, 0.5 mM EDTA, 5 M valinomycin, and 1 M rotenone, pH 7.4) in a cuvette at a final concentration of 0.5 mg/ml mitochondrial protein.…”
Section: Mitochondrial Swelling Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…54 TKPTS cells were seeded in Seahorse 24-well tissue culture plates at a density of 2.5310 4 cells/well and allowed to adhere for 24 hours. Primary cultures of TECs from kidney were grown to confluence on Seahorse 24-well tissue culture plates, as described above.…”
Section: Measurements Of Oxygen Consumption Rate and Mitochondrial Fumentioning
confidence: 99%
“…FCCP was used at two doses and monitored over time because it has a narrow dosing range in which it induces the maximal rate of mitochondrial respiration. 54 OCR was measured in 3-minute periods of time (over a total period of 2 hours). Basal mitochondrial respiration, ATP-linked respiration, proton leak (non-ATP-linked oxygen consumption), maximal respiration, nonmitochondrial respiration, reserve respiratory capacity, respiratory control ratio, and coupling efficiency were determined in whole cells according to Brand et al 29 Three to four wells were used for each experimental group.…”
Section: Measurements Of Oxygen Consumption Rate and Mitochondrial Fumentioning
confidence: 99%